2016
DOI: 10.1038/jp.2016.161
|View full text |Cite
|
Sign up to set email alerts
|

Oral colostrum priming shortens hospitalization without changing the immunomicrobial milieu

Abstract: Background Oral colostrum priming (OCP) after birth in preterm infants is associated with improved weight gain and modification of the oral immuno-microbial environment. We hypothesized OCP would modify salivary immune peptides and the oral microbiota in preterm infants. Methods We conducted a prospective, randomized clinical trial to determine the effects of OCP on salivary immune peptide representation in preterm infants (<32 weeks completed gestation at birth). Saliva samples were collected prior to and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(106 citation statements)
references
References 34 publications
6
96
0
4
Order By: Relevance
“…Similarly, earlier conducted study did not show any significant reduction in the incidence of NEC with OAC. 29,31,32 Similar to the earlier published studies, there was no significant reduction in the incidence of neonatal sepsis in the study population, 29,31,32 but Lee et al showed significant reduction in clinical sepsis in the intervention arm. This difference can be because of difference in the study population of both the trials as neonates of Lee et al trial were more premature and were lighter in weight, compared with our study population.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similarly, earlier conducted study did not show any significant reduction in the incidence of NEC with OAC. 29,31,32 Similar to the earlier published studies, there was no significant reduction in the incidence of neonatal sepsis in the study population, 29,31,32 but Lee et al showed significant reduction in clinical sepsis in the intervention arm. This difference can be because of difference in the study population of both the trials as neonates of Lee et al trial were more premature and were lighter in weight, compared with our study population.…”
Section: Discussionsupporting
confidence: 78%
“…33 Similar to Romano-Keeler et al, we reported significant reduction in the duration of hospital stay in the intervention arm. 31 This reduction can be explained by decrease in the incidence of early onset, late onset, and VAP in the intervention arm, although the differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 89%
“…In part, our result likely reflects the recent change in NICU culture to start trophic feeds as early as possible. 33 In a recent study, Romano-Keeler et al 17 also observed no difference in the time to initiate enteral feeds (median age of 2 days) between groups, further validating this cultural shift. Similar to Lee et al 27 we also found no difference in the time it took for infants to regain their birth weight and no difference in time to reach full enteral feeds.…”
Section: Nutritional Outcomesmentioning
confidence: 81%
“…16 In the immediate postnatal period for very low birth weight (VLWB) infants, enteral feedings are not always possible and oral feedings are not practical because of developmental immaturity. 17 To bridge the gap to the introduction of enteral breast milk, the practice of early application of oropharyngeal colostrum (OC) was proposed as a protective strategy. 18 This application of OC in this early neonatal period is feasible and safe for VLBW infants that are not yet able to receive enteral feeds.…”
Section: Introductionmentioning
confidence: 99%
“…We included 8 RCTs that proved eligible, enrolling 394 individuals. The intervention in 6 studies 13,14,16,[26][27][28] was human colostrum, and in 2 studies the intervention was bovine colostrum. 29,30 In 2 studies, researchers enrolled preterm infants with a birth weight of ≤1.0 kg or gestational age <28 weeks.…”
Section: Description Of Included Studiesmentioning
confidence: 99%